The Role of Hospitals in Supporting the Community Project for Stroke Patient Services in Greater Bangkok - ซื่อเลื่อม เกรียงศักดิ์; ชมพิกุล จิราพร; สุทธิสุคนธ์ ปราณี (Disease Control Journal, 2009)
The increase in the number of stroke patients affected the medical treatment and care expenses of the nation. The Nation Health Security Office (NHSO) and Physical Therapy Council established the Community Project for Stroke Patient Services in Greater Bangkok. The objectives of this study were to evaluate this project, assessing the problems connected with project administration and recommend how to improve and sustain stroke patient services. Data was taken from in-depth interviews and focus groups with hospital administrators and delegates from four hospitals for analysis according to the project goals. The results of the study report that there were 408 patients (only 34% of the project’s set at 1,200 cases). The project attempted to include 16 other hospitals in order to increase the number of patients served, but this was still not able to reach the project goal. There were problems in the referral system with some hospitals because of a lack of formal hospital policy to refer patients to the project, lack of sustained contact by the project with the hospitals, changing in administrators which exacerbated the problem, the limited numbers of doctors, lack of modern medical equipment, lack of funding and lower number of stroke patients. The study recommends an adjustment of the service policy of the project in terms of patient screening, stronger referral of stroke patients from participating hospitals to the project, greater effort at patienthospital-project coordination and advocacy for addressing the problems of stroke patients in the next National Development Plan which would include the establishment of a center specializing in community-based holistic physiotherapy to provide care and enhance vocational concerns of stroke victims.